Polishing layer and method of making same, polishing pad and applications

CN122851464BActive Publication Date: 2026-10-30SHENZHEN XINDEPU TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611365164.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-30
Estimated Expiration
2046-09-04

AI Technical Summary

Technical Problem

[0005]本发明的主要目的是提出一种抛光层及其制备方法、抛光垫及应用,旨在解决现有技术中微凸体耐磨性差、微观接触面积不稳定,抛光性能一般的问题

Benefits of technology

[0016]本发明的技术方案中,本发明的抛光层包括聚氨酯预聚物和固化剂,所述抛光层的表层上嵌设有改性PLGA微球,且所述改性PLGA微球的一端突出所述抛光层设置,以形成微凸体,所述改性PLGA微球表面键合了二氧化硅。本发明的抛光垫包括依次层叠设置的抛光层、中间胶层、缓冲层、背胶层以及离型膜层,本发明提供的抛光垫具有打磨损失率低,抛光效果好的优点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a polishing layer and a preparation method thereof, a polishing pad and application, and relates to the technical field of polishing. The polishing layer comprises a polyurethane prepolymer and a curing agent, modified PLGA microspheres are embedded on the surface layer of the polishing layer, one end of the modified PLGA microspheres protrudes from the polishing layer to form a microconvex body, and the surface of the modified PLGA microspheres is bonded with silicon dioxide. The polishing pad comprises a polishing layer, an intermediate adhesive layer, a buffer layer, a back adhesive layer and a release film layer which are sequentially stacked, and the polishing pad has the advantages of low polishing loss rate and good polishing effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polishing technology, and in particular to a polishing layer, its preparation method, a polishing pad, and its application. Background Technology

[0002] CMP (chemical mechanical polishing) is a technique in which the surface of the workpiece is placed face down, and pressure is applied to a polishing pad. Under the action of polishing fluid, and with the help of the relative movement between the polishing pad and the workpiece, the material on the surface of the workpiece is removed through the mechanical grinding of abrasive particles and the chemical corrosion of oxidants, thereby obtaining a flat surface.

[0003] Existing polishing pads commonly use porous polyurethane materials as the polishing layer. The preparation method typically involves mixing a polyurethane prepolymer with a curing agent, adding hollow polymer microspheres (such as acrylonitrile copolymer microspheres) for foaming, followed by casting, curing, and slicing. The hollow microspheres form a uniformly distributed closed-cell structure within the polyurethane matrix. After surface trimming, the pore walls rupture to form micro-protrusions, creating a microscopic contact surface with the workpiece, thereby achieving material removal. However, under polishing pressure and frictional shearing, plastic deformation and wear easily occur, leading to changes in the micro-protrusion morphology and surface "glazing." This causes the microscopic contact area ratio to exceed a controllable range, resulting in a decrease in polishing rate and processing inhomogeneity.

[0004] Therefore, it is necessary to provide a polishing pad with good wear resistance of micro-protrusions, stability of micro-contact area, and good polishing performance. Summary of the Invention

[0005] The main objective of this invention is to propose a polishing layer and its preparation method, polishing pad and its application, aiming to solve the problems of poor wear resistance of micro-protrusions, unstable micro-contact area and general polishing performance in the prior art.

[0006] To achieve the above objectives, the present invention proposes a polishing layer comprising a polyurethane prepolymer and a curing agent, wherein modified PLGA microspheres are embedded on the surface of the polishing layer, and one end of the modified PLGA microspheres protrudes from the polishing layer to form a micro-protrusion, and the surface of the modified PLGA microspheres is bonded with silicon dioxide.

[0007] In one embodiment, the modified PLGA microspheres have a particle size of 150-500 nm.

[0008] In one embodiment, the polyurethane prepolymer comprises MDI-PPG or TDI-PCL; and / or, The curing agent includes 4,4'-methylenebis(2-chloroaniline) or diethyltoluenediamine.

[0009] In one embodiment, the method for preparing the modified PLGA microspheres includes the following steps: S10. Add 0.5-1 part of polylactic acid-glycolic acid copolymer to 5-10 parts of dichloromethane and stir for 5-15 min to obtain the oil phase. Add 1-5 parts of emulsifier to 10-50 parts of water and mix evenly to obtain the aqueous phase. Add the oil phase to the aqueous phase and stir at 10000-15000 rpm for 1-5 min. Centrifuge, sieve, and collect the solid microspheres. S20. Add 3-8 parts of solid microspheres to 30-80 parts of MES buffer, add 3-8 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 12-18 parts of N-hydroxysuccinimide, react at room temperature for 20-40 min, add 15-30 parts of aminated silica, react for 4-8 h, quench, centrifuge to collect the solid, wash, dry, and obtain modified PLGA microspheres.

[0010] In one embodiment, the aminated silica comprises porous nano-silica containing a slow-release ionic liquid and aminated irregular nano-silica, wherein the ratio of the porous nano-silica containing the slow-release ionic liquid to the aminated irregular nano-silica is 1-2:3-5.

[0011] In one embodiment, the method for preparing the porous nano-silica containing the slow-release ionic liquid includes the following steps: Under a nitrogen atmosphere, 1-10 parts of porous nano-silica were added to 10-100 parts of anhydrous toluene for dispersion, and 1-10 parts of 3-aminopropyltriethoxysilane were added. The mixture was reacted at 85-105℃ for 12-15 h. The solid was collected by centrifugation and washed to obtain aminated porous nano-silica. Mix 5-20 parts of amino polystyrene microspheres, 10-40 parts of ionic liquid and 100-200 parts of methanol evenly, stir at 78-82℃ for 1-3 hours, filter, wash and dry to obtain slow-release ionic liquid. Mix 5-15 parts of aminated porous nano silica, 40-120 parts of anhydrous ethanol and 10-50 parts of dichloromethane, sonicate for 30-60 min, add 2-12 parts of slow-release ionic liquid under nitrogen atmosphere, react at 50-70℃ for 8-14 h, collect the solid by centrifugation, wash, and obtain porous nano silica containing slow-release ionic liquid.

[0012] In one embodiment, the ionic liquid is selected from at least one of methyl acetate-3-methylimidazolium hexafluorophosphate, ethyl acetate-3-methylimidazolium hexafluorophosphate, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-dodecyl-3-methylimidazolium tetrafluoroborate, and N-butyl-3-methylpyridine hexafluorophosphate.

[0013] The present invention provides a method for preparing a polishing layer, comprising the following steps: mixing 80-120 parts of polyurethane prepolymer and 18-24 parts of curing agent; adding 15-30 parts of modified PLGA microspheres during the semi-curing stage; applying pressure to embed the microspheres partially within the polyurethane surface layer; and then continuing to cure to obtain the polishing layer.

[0014] The present invention provides a polishing pad comprising a polishing layer, an intermediate adhesive layer, a buffer layer, a backing adhesive layer and a release film layer stacked sequentially, wherein the polishing layer is the polishing layer described above or prepared by the method described above.

[0015] The present invention also provides an application of a polishing pad, wherein the polishing pad is used in polishing equipment for semiconductors, sapphire, metals or ceramics.

[0016] In the technical solution of this invention, the polishing layer comprises a polyurethane prepolymer and a curing agent. Modified PLGA microspheres are embedded on the surface of the polishing layer, with one end of each microsphere protruding from the polishing layer to form a micro-protrusion. Silica is bonded to the surface of the modified PLGA microspheres. The polishing pad of this invention comprises a polishing layer, an intermediate adhesive layer, a buffer layer, a backing adhesive layer, and a release film layer, sequentially stacked. The polishing pad provided by this invention has the advantages of low grinding loss rate and good polishing effect. Detailed Implementation

[0017] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially. Furthermore, the meaning of "and / or" throughout the text includes three parallel solutions; for example, "A and / or B" includes solution A, or solution B, or a solution where both A and B are satisfied simultaneously. In addition, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0018] Existing polishing pads commonly use porous polyurethane materials as the polishing layer. The preparation method typically involves mixing a polyurethane prepolymer with a curing agent, adding hollow polymer microspheres (such as acrylonitrile copolymer microspheres) for foaming, followed by casting, curing, and slicing. The hollow microspheres form a uniformly distributed closed-cell structure within the polyurethane matrix. After surface trimming, the pore walls rupture to form micro-protrusions, creating a microscopic contact surface with the workpiece, thereby achieving material removal. However, under polishing pressure and frictional shearing, plastic deformation and wear easily occur, leading to changes in the micro-protrusion morphology and surface "glazing." This causes the microscopic contact area ratio to exceed a controllable range, resulting in a decrease in polishing rate and processing inhomogeneity.

[0019] In view of this, the present invention provides a polishing pad, wherein the polishing layer comprises a polyurethane prepolymer and a curing agent, and modified PLGA microspheres are embedded on the surface of the polishing layer, wherein one end of the modified PLGA microspheres protrudes from the polishing layer to form a micro-protrusion, and the surface of the modified PLGA microspheres is bonded with silica.

[0020] In the technical solution of this invention, the polishing layer comprises a polyurethane prepolymer, a curing agent, and modified PLGA microspheres with surface-bonded silica. During semi-curing, the pressurized portion of the microspheres is embedded in the surface of the polishing layer to form micro-protrusions, which contact the object to be polished. The micro-protrusions, reinforced by covalently grafted silica, possess high rigidity and wear resistance. The porous nano-silica containing slow-release ionic liquid continuously releases lubricating and auxiliary oxidation components, improving material removal rate and reducing scratches and roughness. The slow release of the ionic liquid and the porous structure work together to dissipate heat, mitigating frictional temperature rise and ensuring polishing stability.

[0021] In some embodiments of the present invention, the particle size of the modified PLGA microspheres is 150-500 nm, and the particle size of the modified PLGA microspheres can be any range of 150, 300 nm or 500 nm.

[0022] The modified PLGA microspheres, with a particle size of 150-500nm, can form highly uniform and size-controllable micro-protrusions after being partially embedded in the surface of the polishing layer. These micro-protrusions can then make substantial contact with the workpiece being polished, ensuring sufficient mechanical cutting points while avoiding excessively deep scratches or uneven contact pressure caused by overly large protrusions. Furthermore, because the PLGA microspheres are grafted with silica, they can be embedded within the polyurethane, preventing them from falling off during use.

[0023] In some embodiments of the present invention, the polyurethane prepolymer includes MDI-PPG or TDI-PCL; the NCO content of the polyurethane prepolymer needs to be sufficient (≥2.8%) to ensure sufficient crosslinking with the -OH / –NH2 on the filler surface.

[0024] In some embodiments of the present invention, the curing agent includes 4,4'-methylenebis(2-chloroaniline) or diethyltoluenediamine.

[0025] In some embodiments of the present invention, the method for preparing the modified PLGA microspheres includes the following steps: S10. Add 0.5-1 part of polylactic acid-glycolic acid copolymer to 5-10 parts of dichloromethane and stir for 5-15 min to obtain the oil phase. Add 1-5 parts of emulsifier to 10-50 parts of water and mix evenly to obtain the aqueous phase. Add the oil phase to the aqueous phase and stir at 10000-15000 rpm for 1-5 min. Centrifuge, sieve, and collect the solid microspheres. S20. Add 3-8 parts of solid microspheres to 30-80 parts of MES buffer, add 3-8 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 12-18 parts of N-hydroxysuccinimide, react at room temperature for 20-40 min, add 15-30 parts of aminated silica, react for 4-8 h, quench, centrifuge to collect the solid, wash, dry, and obtain modified PLGA microspheres.

[0026] PLGA microspheres were prepared by an emulsification-solvent evaporation method. Then, the carboxyl groups at the ends of the PLGA molecular chains were activated to make them highly active intermediates. These intermediates then underwent a stable amidation reaction with the amino groups on the surface of aminated silica to form covalent bonds, thereby firmly grafting aminated silica nanoparticles onto the surface of the microspheres. The resulting modified PLGA microspheres were partially embedded in the surface of the polishing layer to form micro-protrusions. The grafted silica nanoparticles can prevent and reduce direct contact between the polishing pad and the workpiece, making the pressure distribution more uniform. During operation, they can prevent abrasive agglomeration and increase the workpiece removal rate. The gaps formed by the contact between the micro-protrusions and the workpiece are more conducive to the flow and renewal of the polishing fluid, improving polishing efficiency and surface smoothness.

[0027] In some embodiments of the present invention, the aminated silica includes porous nano-silica containing a slow-release ionic liquid and aminated irregular nano-silica; the ratio of the porous nano-silica containing the slow-release ionic liquid to the aminated irregular nano-silica is 1-2:3-5.

[0028] Porous nano-silica containing slow-release ionic liquid is loaded with slow-release ionic liquid. During use, the slow-release ionic liquid can increase the polishing rate. Aminated irregular nano-silica has greater rigidity than porous nano-silica containing slow-release ionic liquid, mainly to enhance the cutting ability of micro-protrusions and improve the polishing rate through physical action.

[0029] In some embodiments of the present invention, the method for preparing the porous nano-silica containing the slow-release ionic liquid includes the following steps: Under a nitrogen atmosphere, 1-10 parts of porous nano-silica were added to 10-100 parts of anhydrous toluene for dispersion, followed by 1-10 parts of 3-aminopropyltriethoxysilane. The reaction was carried out at 85-105℃ for 12-15 h. The solid was collected by centrifugation and washed to obtain aminated porous nano-silica. Amino groups were grafted onto the nano-silica using 3-aminopropyltriethoxysilane, and the grafted amino groups can be used in subsequent reactions. Mix 5-20 parts of aminopolystyrene microspheres, 10-40 parts of ionic liquid and 100-200 parts of methanol evenly, stir at 78-82℃ for 1-3 hours, filter, wash and dry to obtain a sustained-release ionic liquid; use aminopolystyrene microspheres as a carrier, load the ionic liquid into its pores by heating and stirring to form a sustained-release complex, which will release the ionic liquid during subsequent use. Mix 5-15 parts of aminated porous nano-silica, 40-120 parts of anhydrous ethanol and 10-50 parts of dichloromethane, sonicate for 30-60 min, add 2-12 parts of slow-release ionic liquid under nitrogen atmosphere, react at 50-70℃ for 8-14 h, collect the solid by centrifugation, wash, and obtain porous nano-silica containing slow-release ionic liquid. Mix the slow-release ionic liquid with aminated porous silica, and use the electrostatic / hydrogen bonding between the amino groups on the silica surface and the polystyrene microspheres or ionic liquid to firmly fix the slow-release system in the pores of the porous silica.

[0030] During the polishing process, porous silica slowly releases ionic liquid through its channels, which acts in situ in the contact area to assist mechanical grinding and improve material removal rate. At the same time, the slow-release property avoids surface corrosion or scratches caused by excessive chemical action, thus improving surface smoothness.

[0031] In some embodiments of the present invention, the ionic liquid is selected from at least one of 1-methyl acetate-3-methylimidazolium hexafluorophosphate, 1-ethyl acetate-3-methylimidazolium hexafluorophosphate, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-dodecyl-3-methylimidazolium tetrafluoroborate, and N-butyl-3-methylpyridine hexafluorophosphate. The ionic liquid may be one, two, more, or a combination of all of the above.

[0032] Ionic liquids are encapsulated inside gel microspheres and released slowly during polishing. This assists the oxidant in accelerating the formation of the surface oxide layer and reducing the cutting force required for mechanical removal. The ionic liquids form a lubricating film at the friction interface, reducing the coefficient of friction between the abrasive and the workpiece surface, and minimizing frictional heat and mechanical damage. The continuous and controllable release of the ionic liquids through microsphere encapsulation avoids concentration fluctuations caused by one-time addition.

[0033] In some embodiments of the present invention, the method for preparing the polishing layer includes the following steps: mixing 80-120 parts of polyurethane prepolymer and 18-24 parts of curing agent, adding 15-30 parts of modified PLGA microspheres during the semi-curing stage, applying pressure to partially embed the microspheres in the polyurethane surface layer, and then continuing to cure to obtain the polishing layer.

[0034] During the semi-cured stage, the polyurethane is still in a viscoelastic state. Applying pressure allows the microspheres to be partially embedded in the surface layer, rather than being completely buried or exposed. As curing continues, the polyurethane will fix the embedded parts of the microspheres, preventing them from falling off during polishing and ensuring durability. At the same time, the microspheres are grafted with silica, which increases the contact area with the polyurethane and prevents them from falling off during use.

[0035] The present invention also provides a polishing pad, comprising a polishing layer, an intermediate adhesive layer, a buffer layer, a backing adhesive layer and a release film layer stacked sequentially, wherein the polishing layer is the polishing layer described above or prepared by the method described above.

[0036] The intermediate adhesive layer combines the polishing layer and the buffer layer, ensuring effective transmission of polishing pressure. The buffer layer absorbs localized stress, preventing workpiece damage. The backing adhesive layer and release film layer facilitate easy installation of the polishing pad. The release film protects the adhesive surface from damage during storage and transportation, ensuring strong adhesion and flatness during use. This assembly method is simple and produces stable interlayer interfaces.

[0037] The present invention also provides an application of a polishing pad, wherein the polishing pad is used in polishing equipment for semiconductors, sapphire, metals or ceramics.

[0038] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not intended to limit the present invention.

[0039] Experimental materials The intermediate adhesive layer and the backing adhesive layer were purchased from Sekisui Chemicals and 3M. The buffer layer is made of polyurethane-impregnated nonwoven fabric (SUBA IV); The release film was purchased from Sticco. Polyurethane prepolymer: Covestro Suprasec® 2024 (MDI-terminated PPG type, NCO content 3.8wt%). Test the NCO content before use and store in a sealed container to prevent moisture absorption. Amino polystyrene microspheres: 40nm particle size, purchased from Nanjing Jike Biotechnology Co., Ltd., product number: JK-05-006-040.

[0040] The porous nano-silica is a self-made irregular porous nano-silica with a pore size of 70 nm. The preparation method is as follows: W powder and Si powder are weighed at an atomic ratio of 1:2, and then both are placed in a vacuum ball mill jar for ball milling for 5 hours. The ball milling time is 15:1, and the process control agent is anhydrous ethanol, with an addition amount of 5 wt%. The ball-milled powder is then placed in a graphite mold with a diameter of 10 mm and subjected to discharge plasma sintering. The heating rate is 50 °C / min, the sintering temperature is 1500 °C, the holding time is 5 min, and the holding pressure is 50 MPa. Subsequently, it is naturally cooled to room temperature. Finally, the sintered body is placed in a high-temperature furnace for oxidation heat treatment at 1000 °C for 5 hours in an air atmosphere, and then naturally cooled to room temperature.

[0041] Aminated irregular nano silica was obtained by reacting irregular nano silica (purchased from Hubei Huifu Nanomaterials Co., Ltd. HL-150) with 3-aminopropyltriethoxysilane.

[0042] All other raw materials with indicated sources are commercially available.

[0043] Example 1 A polishing pad, comprising the following steps: Double-sided adhesive is used for the intermediate adhesive layer and the back adhesive layer. The polishing layer and the buffer layer are bonded together using the intermediate adhesive. The back adhesive layer is then bonded to the other side of the buffer layer (the side where the polishing layer is not bonded), and the release film layer is bonded to the other side of the back adhesive layer to obtain the polishing pad.

[0044] The method for preparing the polishing layer includes the following steps: mixing 100 parts of Covestro Suprasec® 2024 and 20 parts of diethyltoluene diamine, adding 20 parts of modified PLGA microspheres during the semi-curing stage, applying pressure to embed the microspheres partially within the polyurethane surface layer, and then continuing to cure to obtain the polishing layer.

[0045] The preparation method of the modified PLGA microspheres includes the following steps: S10, 0.5 parts of polylactic acid-glycolic acid copolymer are added to 8 parts of dichloromethane and stirred for 10 min to obtain an oil phase; 3 parts of emulsifier are added to 40 parts of water and mixed evenly to obtain an aqueous phase; the oil phase is added to the aqueous phase and stirred at 12000 rpm for 4 min; centrifuged, sieved, and the solid microspheres are collected. S20. Add 5 parts of solid microspheres to 50 parts of MES buffer, add 5 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 16 parts of N-hydroxysuccinimide, react at room temperature for 30 min, add 20 parts of aminated silica (porous nano silica containing slow-release ionic liquid and aminated irregular nano silica in a ratio of 1.5:4), react for 6 h, quench, centrifuge to collect the solid, wash, dry, and obtain modified PLGA microspheres with a particle size of 150 nm.

[0046] The method for preparing the porous nano-silica containing the slow-release ionic liquid includes the following steps: Step 1: Under a nitrogen atmosphere, 5 parts of porous nano silica were added to 60 parts of anhydrous toluene for dispersion, and 7 parts of 3-aminopropyltriethoxysilane were added. The mixture was reacted at 100°C for 13 hours. The solid was collected by centrifugation and washed to obtain aminated porous nano silica. Step 2: Mix 10 parts of amino polystyrene microspheres, 25 parts of 1-ethyl acetate-3-methylimidazolium hexafluorophosphate and 150 parts of methanol evenly, stir at 80°C for 2 hours, filter, wash and dry to obtain a slow-release ionic liquid. Step 3: Mix 6 parts of aminated porous nano silica, 100 parts of anhydrous ethanol and 30 parts of dichloromethane, sonicate for 40 min, add 10 parts of slow-release ionic liquid under nitrogen atmosphere, react at 60℃ for 12 h, collect the solid by centrifugation, wash, and obtain porous nano silica containing slow-release ionic liquid.

[0047] Example 2 A polishing pad, which differs from Example 1 in that the modified PLGA microspheres are 15 parts, and 20 parts of aminated silica are added in step S20 of the preparation method of the modified PLGA microspheres, and the particle size of the modified PLGA microspheres is 300 nm.

[0048] Example 3 A polishing pad, differing from Example 1 in that the modified PLGA microspheres are 30 parts, and 30 parts of aminated silica are added in step S20 of the preparation method of the modified PLGA microspheres, and the particle size of the modified PLGA microspheres is 500 nm.

[0049] Example 4 A polishing pad, differing from Example 1 only in that 20 parts of aminated silica (porous nano silica containing slow-release ionic liquid and aminated irregular nano silica in a ratio of 1:5) are added in step S20 of the preparation method of the modified PLGA microspheres.

[0050] Example 5 A polishing pad, which differs from Example 1 only in that 20 parts of aminated silica (porous nano silica containing slow-release ionic liquid and aminated irregular nano silica in a ratio of 2:3) are added in step S20 of the preparation method of the modified PLGA microspheres.

[0051] Example 6 A polishing pad, differing from Example 1 only in that 20 parts of aminated silica (porous nano silica containing slow-release ionic liquid and aminated irregular nano silica in a ratio of 1:10) are added in step S20 of the preparation method of the modified PLGA microspheres.

[0052] Example 7 A polishing pad, differing from Example 1 only in that 20 parts of aminated silica (porous nano silica containing slow-release ionic liquid and aminated irregular nano silica in a ratio of 15:1) are added in step S20 of the preparation method of the modified PLGA microspheres.

[0053] Example 8 A polishing pad, differing from Example 1 only in that the porous nano-silica containing slow-release ionic liquid in step S20 of the preparation method of the modified PLGA microspheres is replaced with an equal amount of aminated porous nano-silica.

[0054] Comparative Example 1 A polishing pad, differing from Example 1 only in that the preparation method of the polishing layer includes the following steps: mixing 100 parts of Covestro Suprasec® 2024 and 20 parts of diethyltoluene diamine, adding 20 parts of modified PLGA microspheres, and curing to obtain the polishing layer.

[0055] Comparative Example 2 A polishing pad, differing from Example 1 only in that the preparation method of the polishing layer includes the following steps: mixing 100 parts of Covestro Suprasec® 2024 and 20 parts of diethyltoluene diamine, adding 20 parts of PLGA microspheres during the semi-curing stage, applying pressure to partially embed the microspheres within the polyurethane surface layer, and then continuing to cure to obtain the polishing layer.

[0056] Comparative Example 3 A polishing pad, differing from Example 1 only in that the method for preparing the polishing layer includes the following steps: mixing 100 parts of Covestro Suprasec® 2024 and 20 parts of diethyltoluene diamine, and curing to obtain the polishing layer.

[0057] Performance testing The test subjects were the polishing pads prepared in Examples 1-8 and Comparative Examples 1-3, and the test items are as follows: Grinding loss: 100 grit sandpaper was attached to the upper plate of the polishing machine, the speed was 80 r / min, the lower plate of the polishing pad was 40 r / min, and the grinding was carried out for 5 minutes. The mass loss before and after was recorded. The polishing machine was from Shenyang Kejing Automation Equipment Co., Ltd., model UNIPOL-1200S. Surface scratch count: The number of scratches on the surface of the polishing pad is measured in accordance with the standard GB / T 6624-2009 "Visual Inspection Method for Surface Quality of Silicon Polished Wafers". Material removal rate: Polishing experiments were conducted on SiC wafers. The SiC wafers used for polishing were 2-inch 4H-SiC wafers with the C-side having an initial surface roughness of 2 nm. The polishing time was 1 hour. The mass change of the wafer before and after polishing was measured using a precision electronic balance (accuracy of 0.1 mg) to calculate the material removal rate. The surface roughness and morphology changes before and after polishing were measured using a white light interferometer. For each experiment, measurements were taken at four different locations on the same radius, and the average value was taken to evaluate the polishing effect. The polishing results are shown in Table 1.

[0058] Table 1

[0059] As shown in Table 1, among Examples 1-8 and Comparative Examples 1-3, Example 1 exhibits the best polishing effect. This is likely because Example 1 incorporates 20 parts of modified PLGA microspheres grafted with aminated silica containing a slow-release ionic liquid. The ratio of porous nano-silica to irregular nano-silica is 1.5:4. This appropriate grafting density ensures sufficient rigidity and chemical slow-release sites on the microsphere surface, enhancing both physical cutting ability and aiding oxidation and lubrication through the continuous release of the ionic liquid, thereby significantly improving material removal rate and reducing surface roughness. Furthermore, the grafted silica, while improving removal rate and reducing surface roughness, is partially embedded in the polyurethane, making the modified PLGA microspheres less prone to detachment.

[0060] The polishing effect of Examples 1-5 is better than that of Examples 6-8. This may be because in Example 6, the ratio of porous nano-silica containing slow-release ionic liquid to aminated irregular nano-silica is 1:10, which reduces the proportion of porous nano-silica containing slow-release ionic liquid. The insufficient release of ionic liquid weakens the lubrication and auxiliary oxidation effects, thus reducing the polishing effect. In Example 7, the ratio of porous nano-silica containing slow-release ionic liquid to aminated irregular nano-silica is 15:1, which increases the proportion of porous nano-silica containing slow-release ionic liquid. The proportion of aminated irregular nano-silica with higher rigidity decreases, resulting in insufficient physical cutting ability of micro-protrusions. In Example 8, the porous nano-silica containing slow-release ionic liquid is replaced with aminated porous nano-silica. Without the addition of porous nano-silica containing slow-release ionic liquid, the lack of lubrication and chemical auxiliary oxidation effects from the ionic liquid will lead to increased polishing pad wear, increased number of scratches, decreased material removal rate, and increased surface roughness of the workpiece.

[0061] The polishing effect of Comparative Examples 1-3 is lower than that of Examples 1-8, possibly because: in Comparative Example 1, modified PLGA microspheres were directly blended into the polyurethane matrix, and most of the microspheres were encapsulated by the matrix, making it difficult to form effective exposed micro-protrusions that directly contacted the polyurethane matrix, resulting in a lower loss rate and polishing effect; in Comparative Example 2, only unmodified PLGA microspheres were used, and the surface of the microspheres was not reinforced with silica, resulting in poor rigidity and easy wear and deformation; in Comparative Example 3, a pure polyurethane polishing layer was used, without the constructed micro-protrusion structure, resulting in weak mechanical cutting ability and a lower polishing effect.

[0062] The above are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the patent protection scope of the present invention.

Claims

1. A polished layer, characterized in that, The polishing layer comprises a polyurethane prepolymer and a curing agent. Modified PLGA microspheres are embedded on the surface of the polishing layer, and one end of the modified PLGA microspheres protrudes from the polishing layer to form micro-protrusions. Silica is bonded to the surface of the modified PLGA microspheres. The particle size of the modified PLGA microspheres is 150-500 nm. The method for preparing the modified PLGA microspheres includes the following steps: S10. Add 0.5-1 part of polylactic acid-glycolic acid copolymer to 5-10 parts of dichloromethane and stir for 5-15 min to obtain the oil phase. Add 1-5 parts of emulsifier to 10-50 parts of water and mix evenly to obtain the aqueous phase. Add the oil phase to the aqueous phase and stir at 10000-15000 rpm for 1-5 min. Centrifuge, sieve, and collect the solid microspheres. S20. Add 3-8 parts of solid microspheres to 30-80 parts of MES buffer, add 3-8 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 12-18 parts of N-hydroxysuccinimide, react at room temperature for 20-40 min, add 15-30 parts of aminated silica, react for 4-8 h, quench, centrifuge to collect the solid, wash, dry, and obtain modified PLGA microspheres. The aminated silica includes porous nano-silica containing slow-release ionic liquid and aminated irregular nano-silica, wherein the ratio of the porous nano-silica containing slow-release ionic liquid to the aminated irregular nano-silica is 1-2:3-5. The method for preparing the porous nano-silica containing the slow-release ionic liquid includes the following steps: Under a nitrogen atmosphere, 1-10 parts of porous nano-silica were added to 10-100 parts of anhydrous toluene for dispersion, and 1-10 parts of 3-aminopropyltriethoxysilane were added. The reaction was carried out at 85-105℃ for 12-15 h. The solid was collected by centrifugation and washed to obtain aminated porous nano-silica. Mix 5-20 parts of amino polystyrene microspheres, 10-40 parts of ionic liquid and 100-200 parts of methanol evenly, stir at 78-82℃ for 1-3 hours, filter, wash and dry to obtain slow-release ionic liquid. Mix 5-15 parts of aminated porous nano silica, 40-120 parts of anhydrous ethanol and 10-50 parts of dichloromethane, sonicate for 30-60 min, add 2-12 parts of slow-release ionic liquid under nitrogen atmosphere, react at 50-70℃ for 8-14 h, collect the solid by centrifugation, wash, and obtain porous nano silica containing slow-release ionic liquid.

2. The polished layer as described in claim 1, characterized in that, The polyurethane prepolymer includes MDI-PPG or TDI-PCL; and / or, The curing agent includes 4,4'-methylenebis(2-chloroaniline) or diethyltoluenediamine.

3. The polished layer as described in claim 1, characterized in that, The ionic liquid is selected from at least one of 1-methyl acetate-3-methylimidazolium hexafluorophosphate, 1-ethyl acetate-3-methylimidazolium hexafluorophosphate, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-dodecyl-3-methylimidazolium tetrafluoroborate, and N-butyl-3-methylpyridine hexafluorophosphate.

4. A method for preparing a polished layer as described in any one of claims 1-3, characterized in that, The method for preparing the polishing layer includes the following steps: mixing 80-120 parts of polyurethane prepolymer and 18-24 parts of curing agent; adding 15-30 parts of modified PLGA microspheres during the semi-curing stage; applying pressure to embed the microspheres partially within the polyurethane surface layer; and then continuing to cure to obtain the polishing layer.

5. A polishing pad, characterized in that, The material comprises a polishing layer, an intermediate adhesive layer, a buffer layer, a backing adhesive layer, and a release film layer, which are sequentially stacked. The polishing layer is the polishing layer according to any one of claims 1-3 or the polishing layer prepared by the preparation method of the polishing layer according to claim 4.

6. An application of the polishing pad as described in claim 5, characterized in that, The polishing pad is used in polishing equipment for semiconductors, sapphire, metals, or ceramics.

Citation Information

Patent Citations

  • Polishing pad, preparation method thereof and manufacturing method of semiconductor device

    CN113442056A

  • Silicon carbide polishing solution and preparation method thereof

    CN122381700A